Development of Interactive Learning Media Based on Articulate Storyline for Teaching Mathematics on Plane Shapes for Grade IV at SDN Baru 02 Pagi - Viola Meika Putri; Kowiyah Kowiyah (Green Publisher Indonesia, 2024)
This study aims to develop interactive learning media based on Articulate Storyline as a medium for learning mathematics flat building material, and to determine the quality of products that have been made so that they are feasible and interesting to use in learning activities with the Research and Development (R & D) research and development method which refers to the ADDIE model or 5 stages in the form of analysis, design, development, implementation and evaluation. The subjects of this study were 25 fourth grade students. The data collection techniques used were observation and questionnaire. Data collection instruments with media validation sheets, material validation sheets, language validation sheets, teacher validation sheets, student response questionnaires. The results of the assessment from the experts are among others: the percentage of media experts 86% shows the criteria